2020
DOI: 10.3892/etm.2020.8717
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic mutations in carbamoyl phosphate synthetase 1 induced hyperammonemia in a neonate: A case report

Abstract: The aim of the present report was to describe the clinical presentation, diagnosis, and treatment of a case of carbamoyl phosphate synthetase 1 (CPS1) deficiency in a neonate, specifically, a 3 day-old female who visited Hunan Provincial People's Hospital due to anorexia and lethargy for 1 day. Physical and laboratory examination, and MRI were undertaken. Whole exome sequencing (WES) was applied for molecular etiology identification. Sanger sequencing was utilized to validate the variants detected by WES. Stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…CPS1 encodes a mitochondrial enzyme named carbamoyl-phosphate synthase 1 that catalyzes synthesis of carbamoyl phosphate from ammonia and bicarbonate. Mutations in this gene have been associated with metabolic deficiencies such as urea cycle disorder and hyperammonemia 53,54 . Individuals with a CPS1 deficiency can present with a wide range of clinical manifestations, including headache, behavioral or psychiatric problems, learning disabilities, sleep disorder, periodic vomiting, seizures, coma, and even death [55][56][57] .…”
Section: Discussionmentioning
confidence: 99%
“…CPS1 encodes a mitochondrial enzyme named carbamoyl-phosphate synthase 1 that catalyzes synthesis of carbamoyl phosphate from ammonia and bicarbonate. Mutations in this gene have been associated with metabolic deficiencies such as urea cycle disorder and hyperammonemia 53,54 . Individuals with a CPS1 deficiency can present with a wide range of clinical manifestations, including headache, behavioral or psychiatric problems, learning disabilities, sleep disorder, periodic vomiting, seizures, coma, and even death [55][56][57] .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the medical history of the neutropenic patients included in the study, only one infant showed a positive history for comorbidities: carbamoyl-phosphate synthetase 1 deficiency (CPS1-D), a disorder of urea cycle metabolism characterised by hyperammonemia that occurs a few days after birth [ 17 ]. However, this pathology is not associated with neutropenia or haematological disorders in general.…”
Section: Resultsmentioning
confidence: 99%